Zerumbone induces G2/M cell cycle arrest and apoptosis via mitochondrial pathway in Jurkat cell line - Rahman, Heshu Sulaiman; Abdullah, Rasedee; Chartrand, Max Stanley; Othman, Hemn Hassan; Yeap, Swee Keong; Namvar, Farideh (Natural Product, 2014)
This investigation determined the anticancer properties of zerumbone (ZER) on the human T-cell (Jurkat) line using the MTT assay, microscopic evaluations, flow cytometric analyses, and caspase activity estimations. The results showed that ZER is selectively cytotoxic to Jurkat cells in a dose and time-dependent manner with IC50 of 11.9 ± 0.2, 8.6 ± 0.5 and 5.4 ± 0.4 μg/mL at 24, 48 and 72 hours of treatment, respectively. ZER did not produce an adverse effect on normal human peripheral blood mononuclear cells (PBMC). ZER is not as cytotoxic as doxorubicin, which imposed an inhibitory effect on Jurkat cells with IC50 of 2.1 ± 0.2, 1.8 ± 0.15, 1.5 ± 0.07 μg/mL after 24, 48 and 72 hours treatment, respectively. ZER significantly (P < 0.05) arrested Jurkat cells at the G2/M phase of the cell cycle. The antiproliferative effect of ZER on Jurkat cells was through the apoptotic intrinsic pathway via the activation of caspase-3 and -9. The results showed that ZER can be further developed into a safe chemotherapeutic compound for the treatment of cancers, especially leukemia.